Implementation of an International Program in Arabic Language Learning to Enhance Speaking Skills for Non-Native Speakers - Murtadho, Ahmad Syafiq; Arifin, Muhammad Syamsul (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Purpose - This study aims to describe the implementation of the International Arabic Language Program (Daurah) conducted by Darunnajah Islamic Boarding School Jakarta in collaboration with Umm Al-Qura University, Makkah Al-Mukarramah, in enhancing the Arabic speaking skills (Maharah Al-Kalam) of non-native Arabic-speaking students enrolled in the Tarbiyatul Mu'allimin wal Mu'allimat Al-Islamiyah program. Design/Methodology/Approach - This study employs a qualitative approach with an instrumental case study design. Data were collected through participatory observation, in-depth interviews with students, supervisors, and native-speaker instructors, and documentation analysis. Thematic analysis was conducted through the stages of data reduction, display, and conclusion drawing, with credibility ensured through source, technique, and time triangulation. Findings - The program yielded significant improvements across three dimensions: increased fluency in daily conversation, enhanced pronunciation and intonation, and expanded vocabulary acquisition. The eclectic teaching method, integrating direct interaction with native speakers, proved to be the primary contributing factor. Among the 43 participants, the program notably increased communicative confidence in both formal and informal settings. Research Limitations/Implications - This study is limited to a two-week program at a single Islamic boarding school, restricting broader generalizability. It is recommended that native speaker interaction be extended beyond the program duration, communicative-based curricula be integrated into regular instruction, and future research explore digital platforms to sustain Arabic speaking practice on a continuous basis.